KARAKTERISTIK MORFOMETRI DAS CIKAPUNDUNG HULU, KABUPATEN BANDUNG, JAWA BARAT - -, Agung Mulyo (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
Upstream watershed Cikapundung or known by the name of Lembang Basin, including the Regency Bandung, West Java. In general, the rock consists of five units (Plistosen Down - Holocene), the Breccia Unit Volcano (Formation Cikapundung), Old Volcano Deposition Unit, tuff unit (Formation Cibeureum), Sandy Tuff Unit (Cikidang Formation) and colluvium. Lembang normal faults trending east-west which is a major fault structure which limits the rate of soil water retention from the Upper Basin watershed Cikapundung Bandung below it. Land classification is characterized by a mixture of rural land in the area of agriculture and plantation, until the presence of centers planned settlements (real estate). Broad watershed is 80.475 km2, around 51.575 kms and the degree of roundness (Rc) = 0.380. Tributaries of the river hierarchy order 1 = 449 types, the order of 2 = 89, the order of 3 = 23, order 4 = 7, the order of 5 = 3 and order 6 = 1 types. Different numbers of streams with stream order 1 and order 2 is very large, causing Rb values of order 1 to 2 becomes large is 5.04. In addition there is a small Rb between orders 4 and 5 is 2.33. Thus, the influence of valley pond clear fault control morphometry study area. Elevation upstream and downstream (estuary) river is generally inversely proportional to the level-order tributaries. Elevation difference between upstream and downstream of all the rivers are relatively the same order. Basin wide average is consistently proportional to the level of orders the river, while the. tributaries frequency (F) is inversely proportional. Kc and the Rc value is below 1, this